2023
DOI: 10.1108/ijtc-07-2022-0175
|View full text |Cite
|
Sign up to set email alerts
|

Backpacker conceptualisation criteria: discussion, clarification and operationalisation proposal

Abstract: Purpose Backpackers can be found all over the world, especially in urban areas where the main enclaves are established. The purpose of this paper is to discuss the operationalisation of the term “backpacker” and present a proposal to conceptualise backpackers and backpackers’ segments based on the operational criteria available in literature to avoid incongruities among researchers. Design/methodology/approach Based on a literature review, this study provides a critical review of the backpacker conceptualisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…Other studies confirmed that recreational attraction has a significant impact on revisit intention (Mahdzar et al, 2015;Markus et al, 2019). In the case of young tourists, with their unique behaviors (Buffa, 2015;Dai et al, 2022) and low travel budgets (Cavagnaro et al, 2018;Martins and Costa, 2023), their perception of water park services are potentially different. Although previous research examined the influence of factors on satisfaction and revisit intention, but did not focus on the influence of attractions on water park visitors' revisit intention.…”
Section: The Relationship Between Water Park Components and Satisfact...mentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies confirmed that recreational attraction has a significant impact on revisit intention (Mahdzar et al, 2015;Markus et al, 2019). In the case of young tourists, with their unique behaviors (Buffa, 2015;Dai et al, 2022) and low travel budgets (Cavagnaro et al, 2018;Martins and Costa, 2023), their perception of water park services are potentially different. Although previous research examined the influence of factors on satisfaction and revisit intention, but did not focus on the influence of attractions on water park visitors' revisit intention.…”
Section: The Relationship Between Water Park Components and Satisfact...mentioning
confidence: 93%
“…Previous studies have explored the behavior, attitudes, and assessment tendencies of young tourists (Buffa, 2015;van Aalst and Brands, 2021) and city parks (Dai et al, 2022;van Aalst and Brands, 2021). Other researchers point out that young tourists are only looking for simple pleasures, having a diverse and increasingly heterogeneous preference for young tourists and low-budget backpackers (Cavagnaro et al, 2018;Martins and Costa, 2023). However, there is no one has focused on criticizing water parks for young tourists, regarding tourist attraction, accessibility, main facilities, and supporting facilities, even though these components are the basic needs of water park services.…”
Section: Literature Review Water Parks and Young Touristsmentioning
confidence: 99%
“…Bearing in mind the heterogeneity of this group [6], research on backpacking tourism has approached the phenomenon from various angles [7]. For instance, Sorensen conducted an ethnographic study [8], while empirical studies have explored it in terms of tourist origins and visited destinations [9].…”
Section: Introductionmentioning
confidence: 99%